New records of nematode parasites from Euryzygomatomys Spinosus (Rodentia, Echimyidae) in Misiones province, Argentina - Robles, Maria del Rosario (2012)
Although three species of nematodes have been recorded from the spiny rat Euryzygomatomys spinosus in Brazil, no helminthes have been recorded from this host in Argentina. Three taxa of nematodes from E. spinosus from Misiones province, Argentina, were identified from the helminthological collection of Museo de La Plata. Host voucher specimens refered to this material were found in the Colección Elio Massoia. The present survey contributes to the knowledge of nematode species from Echimyidae and illustrates the importance of integrating data from helminth and mammal collections.